Pair Interaction Potential Energy Function from the Extended Principle of Corresponding States for SF6-SF6 - Haghighi, B.; Mansoori Oghaz, N.; Najafi, M. (Asian Journal of Chemistry, 2010)
An iterative inversion procedure is used to obtain the effective isotropic part of the pair-interaction potential for SF6-SF6 from the extended principle of corresponding states. The Lennard-Jones (12-6) potential energy function is used as the initial model potential required by the method. Over a range of reduced temperature extending from 1 to 1000 this directly measured potential for SF6-SF6 fully agrees with the Hartree-Fock-Dispersion (HFD)-type and Morse-Morse-Spline-vander Waals (MMSV)-type independently known potentials. This accurate inverted potential can be used in the calculation of the orientation-averaged viscosity collision integrals and the dimensionless ratios which are essential to calculate other transport properties. Our method can be applied to calculate the pair-interaction potential with no need for force fitting data and lengthy multi-parameter fitting procedure in all temperature ranges.